2009
DOI: 10.1038/aps.2009.135
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin attenuates homocysteine-induced apoptosis in human umbilical vein endothelial cells via inhibiting NADPH oxidase-related oxidative stress-triggered p38MAPK signaling

Abstract: Aim:To examine the effect of atorvastatin on homocysteine (Hcy)-induced reactive oxygen species (ROS) production and apoptosis in human umbilical vein endothelial cells (HUVECs). Methods: HUVECs were cultured with Hcy (0.1−5 mmol/L) in the presence or absence of atorvastatin (1−100 μmol//L) or various stress signaling inhibitors, including the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase inhibitor diphenylene iodonium (DPI, 10 μmol/L), the p38 mitogen-activated protein kinase (p38 MAPK) inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…Recently, clinical study has indicated that atorvastatin decreases circulating CXCL12, an angiogenic chemokine, in patients with coronary artery disease, congestive heart failure, and (or) myocardial infarction, without affecting the plasma lipid profile (Camnitz et al 2012). Atorvastatin showed anti-senescence and anti-apoptotic actions in human umbilical vein endothelial cells (HUVECs) exposed to oxidative stress (Bao et al 2009;Ota et al 2010). Thus, atorvastatin protects endothelial cells and has restorative pleiotropic effects.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, clinical study has indicated that atorvastatin decreases circulating CXCL12, an angiogenic chemokine, in patients with coronary artery disease, congestive heart failure, and (or) myocardial infarction, without affecting the plasma lipid profile (Camnitz et al 2012). Atorvastatin showed anti-senescence and anti-apoptotic actions in human umbilical vein endothelial cells (HUVECs) exposed to oxidative stress (Bao et al 2009;Ota et al 2010). Thus, atorvastatin protects endothelial cells and has restorative pleiotropic effects.…”
Section: Introductionmentioning
confidence: 98%
“…Short-term atorvastatin treatment in patients with CAD was reported to be regenerative on the endothelium, through the inhibition of endothelial apoptosis (Schmidt-Lucke et al, 2010), even induced by hyperhomocysteinemia (Bao et al, 2009). On the other hand, high micromolar concentrations of statins, 100-to 200-fold higher than serum statin levels in patients, have been reported to induce apoptosis (Katsiki et al, 2010).…”
Section: B Statins and Endothelial Functionmentioning
confidence: 99%
“…Statins have been found to reduce oxidative stress-induced apoptosis of endothelial cells [1] and restore the survival and function of EPCs [13,18,23] . These effects may contribute to both ischemia-induced neovascularization and endothelial regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has found that Hcy may induce ROS accumulation and endothelial cell apoptosis in human umbilical vein endothelial cells (HUVECs) via activating NADPH oxidase-related oxidative stress and the p38MAPK signaling pathway [1] . Recent studies have suggested that endothelial progenitor cells (EPCs) may contribute to neovasculogenesis and reendothelialization of damaged blood vessels to maintain the endothelium [2,3] .…”
Section: Introductionmentioning
confidence: 99%